2020
DOI: 10.1097/mop.0000000000000960
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric delirium: epidemiology and outcomes

Abstract: Purpose of review Delirium is a frequent complication of serious medical illness in children. The purpose of this review is to highlight recent data on the epidemiology and outcomes related to pediatric delirium, and discuss prevention strategies. Recent findings Delirium rates in the pediatric ICU are greater than 25%. Delirium in children is associated with prolonged mechanical ventilation and hospital length of stay, increased costs, and excess morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 54 publications
3
46
0
2
Order By: Relevance
“…Delirium incidence in our unit was 23%, with hypoactive delirium as the most common phenotype (75%). Delirium incidence was similar with the one reported by other medical PICUs ( 15 , 28 , 36 ). In the majority of the cases, delirium was treated with non-pharmacologic interventions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Delirium incidence in our unit was 23%, with hypoactive delirium as the most common phenotype (75%). Delirium incidence was similar with the one reported by other medical PICUs ( 15 , 28 , 36 ). In the majority of the cases, delirium was treated with non-pharmacologic interventions.…”
Section: Discussionsupporting
confidence: 89%
“…In the last decade, advances in pediatric critical care significantly decreased mortality rates, however, this paralleled with an increase of children surviving with important functional morbidities ( 13 , 28 ). Delirium is a common complication of pediatric critical illness and favors the development of p-PICS ( 5 ), thus, strategies to reduce delirium risk factors, such as prolonged immobilization and benzodiazepine use ( 10 , 28 , 31 , 32 ), are now recommended by the Society of Critical Care Medicine ICU Liberation Campaign ( 10 ) to ensure optimal functional recovery in children after PICU stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with pain and sedation, regular assessment by using validated tools is the key for adequate management. Delirium remains underdiagnosed and misinterpreted in children and therefore undertreated, especially as children in hypoactive delirium are often seen as just especially calm and “easy” to comfort ( 58 ). All children admitted to a PICU should be subject to routine screening for withdrawal and early detection of symptoms and diagnosis of both hypo- and hyperactive as well as mixed forms of delirium in children…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated a consistent and robust association between exposure to benzodiazepines and delirium development in pediatric critical illness [ 1 , 2 , 3 , 4 , 5 ]. As pediatric delirium is related to poor outcomes (including increased duration of mechanical ventilation, increased ICU and hospital length of stay, and even excess mortality), there is a compelling need to explore alternatives to benzodiazepine-based sedation in mechanically ventilated children [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%